G(-2)=4(-2)-3

Simple and best practice solution for G(-2)=4(-2)-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for G(-2)=4(-2)-3 equation:


Simplifying
G(-2) = 4(-2) + -3

Reorder the terms for easier multiplication:
-2G = 4(-2) + -3

Multiply 4 * -2
-2G = -8 + -3

Combine like terms: -8 + -3 = -11
-2G = -11

Solving
-2G = -11

Solving for variable 'G'.

Move all terms containing G to the left, all other terms to the right.

Divide each side by '-2'.
G = 5.5

Simplifying
G = 5.5

See similar equations:

| (9x-3)/6=5/2 | | y/5-7=-2 | | t^2/2+t^2 | | 13a-45+a= | | 4x+4x(.05)=105.00 | | 62.9296(y-100)+64.9278y=63.546 | | -286=4(1+8r)+2r | | 4x+8=x | | 3(x+5)(x+5)=60 | | 2h+9=-2+3(3h+6) | | x+0.3=11 | | 3x+17=7x-5 | | -9-(4+10)+20= | | -2.3=2.4z+1.3 | | 8y+7=1-2(3y-3) | | 3.9m-4.2=-1.1(4m+8) | | F(5)=-2(5)+3 | | 180=-6(4v+2) | | 62.9296(100-y)+64.9278y=63.546 | | x^4-12x^3-38x^2+300x-275=0 | | 7y+2x+3=20+2x | | 9x-3=5/2 | | 3x+4/7-5x-3/7=6/7 | | F(5)=-2x+3 | | 9x^2-61x+4=0 | | 3-4x/5=-9 | | 5(3r-1)-(r-1)=1+5+3r-5 | | -2v+10= | | -(1+7v)-7v=111 | | 9=2-5x | | 1/3(5/3) | | 2x^4+x^2+5x+12=0 |

Equations solver categories